MOG - A smart mobile system for interactive museum visits - Coitos, B.; Serrão, C.; Garrido, N. (Multi Conference on Computer Science and Information Systems, MCCSIS 2019 - Proceedings of the International Conferences on ICT, Society and Human Beings 2019, Connected Smart Cities 2019 and Web Based Communities, 2019)
In this work we propose an integrated system to manage and enhance the museums visiting experience for the general public, providing a more comfortable, intelligent and interactive way to visit multiple museums without the need for several mobile applications, whilst giving a tool to museum curators that allows them to easily manage and extend the content displayed to each individual visitor. For that purpose, our approach was to develop a single mobile application, a module to an open-source Content Management System (CMS), namely Drupal 8, and incorporate location information inferred by the capture of BLE's signals (beacons). The proposed prototype features an Android application that will be used by the visitors where they can access the available information about several museums, and combined with BLE's, will display information about the museum and spaces of the museum where the visitor is (or is planning to visit). This application gives the option to choose from several languages that are provided and managed by each museum.